Degradation mechanisms of oxytetracycline in the environment - Zhao-jun LI; Wei-ning QI; Yao FENG; Yuan-wang LIU; Shehata Ebrahim; Jian LONG (Journal of Integrative Agriculture, 2019)
Over the past few decades, the usage of oxytetracycline (OTC), a kind of antibiotic, has increased with the development of aquaculture and livestock breeding. However, about 30–90% of the applied antibiotics are excreted as the parent compounds into the environment, especially with the application of animal manure to agricultural fields. This large influx of antibiotics may lead to the destruction of the natural microbial ecological community and pose great threats to human beings through the food chain. Therefore, the fate and toxicity of OTC in the environment are issues of great concern. Degradation of OTC, including the non-biodegradation and biodegradation, and the biological toxicity of its degradation products or metabolites, are reviewed in this paper. The non-biodegradation pathways include hydroxylation, quinonization, demethylation, decarbonylation, dehydration and secondary alcohol oxidation. Light (particularly UV light), pH and oxidizing substances play important roles in non-biodegradation. Biodegradation products include 4-epi-OTC (EOTC), 2-acetyl-2-decarboxy-amido-OTC (ADOTC), α-apo-OTC and β-apo-OTC. EOTC is an epimer and identied except for the configuration of the C4 dimethylamino group of OTC. Temperature and pH are the main factors affecting biodegradation pathways of OTC. In addition, this review discusses concerns over the biological toxicity of OTC degradation products.